Reestablishment of Amblyomma tenellum Koch, 1844 (Acari: Ixodidae) - Nava, Santiago (2014)
Herein, Amblyomma tenellumKoch, 1844 (Ixodidae) is reestablished as a valid tick name and removed from the synonymy list of Amblyomma cajennense (Fabricius, 1787), while Amblyomma imitatorKohls, 1958, is relegated to a junior synonym of A. tenellum. Amblyomma tenellum is redescribed based on the examination of male type specimens collected by Deppe at the beginning of the 19th century in Mexico and described by Koch in 1844.